2006
DOI: 10.1097/01.tp.0000230459.22968.26
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Cytomegalovirus Prophylaxis in Solid Organ Transplantation

Abstract: The benefits of cytomegalovirus (CMV) prophylaxis in preventing the direct effects of CMV infection and disease are well established; however, the impact of exposure to antiviral agents on preventing the indirect effects of CMV infection are poorly defined. This article reviews the results of current studies demonstrating the benefits of CMV prophylaxis in reducing the risks of indirect effects of CMV infection: acute and chronic allograft rejection, graft failure, patient mortality, cardiac complications and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…The finding that CMV D+R- recipients fared better was a surprise finding of the study and is largely unexplained. Most studies show that these recipients are at increased risk of both death and graft loss [17]. All patients would have received prophylaxis at both centers.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that CMV D+R- recipients fared better was a surprise finding of the study and is largely unexplained. Most studies show that these recipients are at increased risk of both death and graft loss [17]. All patients would have received prophylaxis at both centers.…”
Section: Discussionmentioning
confidence: 99%
“…Although these 'radical' cases have brought significant attention to the transplant community and the public due to the intense media coverage, one must bear in mind that still by far more organ recipients die from consequences associated with the transmission of cytomegalovirus and EBV than all other viruses together. For many viruses reliable prophylaxis is now available and if appropriate allocation is performed these grafts have a good chance for long-term survival [132,[134][135][136]. This knowledge should be considered and in order to optimize the utilization and survival of viral infected grafts, one may consider overriding the Model for End-stage Liver Disease (MELD) allocation system in some cases.…”
Section: Resultsmentioning
confidence: 99%
“…In Turkey, results in terms of renal function and BPAR were consistently better in all four treatment groups compared with that in the overall study population, probably in part because fewer patients were infected with CMV; some studies have demonstrated a link between CMV infection and acute rejection [10]. In the interpretation of these figures, one should take into account that the definition of CMV infection was left to the discretion of the investigators and may have varied among countries.…”
Section: Discussionmentioning
confidence: 98%